Exploring The Perceptions Of College Students Regarding Radicalism And Extremism: A Qualitative Study - Sri Mulyani Nasution; Dede Rosyada; Darin Brenda Iskarina (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2023)
Public understanding of radicalism seems to be different. For many people, radicalism has even become a sensitive issue and is sometimes reluctant to be discussed. The assumption that educational institutions are not immune to the influence of radical ideologies is reinforced by several research results. Meanwhile, students do not get an optimal understanding of religion through Islamic Religious Education (PAI) because of the lack of reading material for PAI subject matter with content that can strengthen national character and values ​​in addition to monotonous and unvaried teaching methods that make students less attention to PAI teaching. This study wants to see a picture of students' understanding of radicalism. The research was conducted with a qualitative approach. The results showed that the average respondent could not distinguish what was radical and what was radicalism. Some respondents disagreed with the notion that Islam was related to radicalism and respondents understood that radicalism was different or had nothing to do with the Caliphate state.